2014
DOI: 10.1177/1367877913519308
|View full text |Cite
|
Sign up to set email alerts
|

Witnesses of a cultural crisis: Representations of media-related metaprocesses as professional metacriticism of arts and cultural journalism

Abstract: Arts and cultural journalism have been found in numerous debates during recent decades to struggle in the midst of a crisis. This article traces the recorded discourse of professionalism that considers cultural journalism to be in a state of decline. A literature review on academic research and contributions in public debates provides an insight into the 'crisis talk' of the last two decades and unveils general controversies in the development of the professional culture of cultural journalism. By mapping the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
0
22
0
1
Order By: Relevance
“…The results showed that the discourse on cultural journalism was tightly linked to the idea of non-preferred or notorious change (see Constantopoulou, 2016;Frey, 2014;Jaakkola, 2015b). The number of articles about the crisis indicates that it is a reoccurring frame.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The results showed that the discourse on cultural journalism was tightly linked to the idea of non-preferred or notorious change (see Constantopoulou, 2016;Frey, 2014;Jaakkola, 2015b). The number of articles about the crisis indicates that it is a reoccurring frame.…”
Section: Resultsmentioning
confidence: 97%
“…It is not too unrealistic to think that the crisis frame has been adopted in order to make culture topical, interesting and thus relevant as a journalistic issue. It then functions as an entry point into the public discussion (Jaakkola 2015b). Simultaneously, the entry into public discussion is part of the self-interested behaviour of participants involved in the production of the discourse (Fengler & Ruß-Mohl, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Third, a significantly large number of cultural reporters are freelancers who are only occasionally involved in journalistic production. Instead, they are artists or other art professionals, enthusiasts and amateurs, or connoisseurs in a certain artistic or cultural field (Harries and Wahl-Jorgensen 2007;Jaakkola 2014b;Janssen 1997;Klein 2005). …”
Section: Arts Exceptionalism and Production Structurementioning
confidence: 98%
“…It may also become more susceptible to external pressures "liquefying" the ethics. For example, commercialization and the professionalization of cultural PR have seemingly necessitated cultural journalists' creating an agenda of their own, an agenda of critical cultural journalism that would act as a counterforce against commercialization (Elkins 2003;Jaakkola 2014b;Olsen 2014). …”
Section: Ethical Orientationmentioning
confidence: 98%
“…when making decisions about how to put together an article -this assuming that what constitutes the public interests are well defined. As Jaakkola (2014Jaakkola ( : 547, 2015 notes, cultural journalists are faced with striking a balance between the commercial and aesthetic implications of their work. The book reviewers I interviewed emphasized that their goal for writing reviews was not to sell books but to inform the general public about new books as part of a broader cultural conversation.…”
Section: Self-interestmentioning
confidence: 99%